2012
DOI: 10.1163/156854111x597485
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the nematicide oxamyl under field and laboratory conditions

Abstract: The persistence of nematicides such as oxamyl can vary greatly in field conditions. The objectives of the present studies were: i) to compare oxamyl degradation in soils with different properties; ii) to quantify and examine the influence of various abiotic factors on oxamyl degradation; iii) to establish the validity of using simulated models to predict the degradation in the field; and iv) to examine if a second application of oxamyl to the same soil 13 or 26 weeks after the first application enhances degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This might be attributed to the long hatching period of G. pallida compared with that of G. rostochiensis contributing to its presence in the soil over a long period, extending the time when most of the active substance of oxamyl has been degraded. It was shown that after incorporation, the con centration of granular nematicides, e.g., oxamyl, will de crease due to degradation of the nematicide, which could be influenced by the environment (e.g., temperature), soil properties and microbial activities in the soil (Smelt et al, 1987;Haydock et al, 2012). This chemical could persist in the soil for 28-91 days after application (Haydock et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the long hatching period of G. pallida compared with that of G. rostochiensis contributing to its presence in the soil over a long period, extending the time when most of the active substance of oxamyl has been degraded. It was shown that after incorporation, the con centration of granular nematicides, e.g., oxamyl, will de crease due to degradation of the nematicide, which could be influenced by the environment (e.g., temperature), soil properties and microbial activities in the soil (Smelt et al, 1987;Haydock et al, 2012). This chemical could persist in the soil for 28-91 days after application (Haydock et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of pesticide applications is also an important factor that can affect such degradation (Harrison, 1990). Nevertheless, the degradation of xenobiotic compounds by members of the soil microflora is an important means by which said compounds Smelt et al (1987); Haydock et al (2012) * Currently not available, and prohibited from January 2014 ** Trade name of generic products *** Plums excluded are removed from the environment, and thus prevented from becoming pollution-related problems (Karns et al, 1986). The involvement of microorganisms in the degradation of fenamiphos was proven in a study conducted by Stirling et al (1992).…”
Section: Biological Factorsmentioning
confidence: 99%
“…Therefore, whereas oxamyl concentrations in soil were likely higher in April than May or June, potentially this difference was not as large due soil temperatures being .108C at all application dates. Soil type is another factor that can impact oxamyl degradation and absorption (Barmilow et al, 1980;Haydock et al, 2012). Our trials encompassed several different soil types (loam, sandy loam, silt loam) and we did not observe any noticeable differences in oxamyl efficacy across these soil type.…”
Section: Discussionmentioning
confidence: 69%